2021
DOI: 10.1021/acs.oprd.1c00223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of BACE1 Inhibitors E2609/E2071 via Oxime–Olefin Cycloaddition Following a Process Risk Mitigation Strategy

Abstract: Process development of E2609 from the preclinical stage to the clinical stage following a process risk mitigation strategy is described here. Key features include a turbo Grignard reaction monitored by in-situ IR, [3 + 2] cycloaddition in water, chemoselective amide coupling via in-situ protection, and a Reformatsky/decarboxylation approach to install a difluoromethyl group. Toward safe and scalable manufacture of E2071, an analog of E2609, a flow-reaction process for trifluoromethylation of aldehydes is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Kim et al reported the manufacturing synthesis of E2609 and E2071, potent orally administered β-amyloid cleaving enzyme 1 (BACE1) inhibitors, using a newly developed flow trifluoromethylation reaction of acrolein with Me 3 SiCF 3 in 2022 (Figure 26). [41] They found that the addition of tetrabutylammonium fluoride to a solution of acrolein and Me 3 SiCF 3 rapidly reacted, however, the temperature in the reaction changed almost instantly even on a small scale. Therefore, scaling up the batch process for catalytic trifluoromethylation is difficult.…”
Section: Ruppert-prakash Reagent (Me 3 Sicf 3 )mentioning
confidence: 99%
“…Kim et al reported the manufacturing synthesis of E2609 and E2071, potent orally administered β-amyloid cleaving enzyme 1 (BACE1) inhibitors, using a newly developed flow trifluoromethylation reaction of acrolein with Me 3 SiCF 3 in 2022 (Figure 26). [41] They found that the addition of tetrabutylammonium fluoride to a solution of acrolein and Me 3 SiCF 3 rapidly reacted, however, the temperature in the reaction changed almost instantly even on a small scale. Therefore, scaling up the batch process for catalytic trifluoromethylation is difficult.…”
Section: Ruppert-prakash Reagent (Me 3 Sicf 3 )mentioning
confidence: 99%